Menjaga Toleransi Melalui Pedidikan Multikulturalisme - Muhammad Ridwan Effendi; Yoga Dwi Alfauzan; Muhammad Hafizh Nurinda (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2021)
Multicultural education is the Indonesian education system that began even during the time of Ki Hajar Dewantara. This education system is able to end the view of differences between race, religion, ethnicity, culture, language and so on if it is implemented properly. In various cases in Indonesia, attitudes of intolerance often spice up the problem. Through this multicultural education, it is hoped that it will be able to provide a deep meaning to this attitude of tolerance. This research was conducted using the literary method obtained from library data, books, journals, websites, and all other library sources. The type of research the writer uses is qualitative research, where the research is carried out through a narrower but deeper scope. The author will describe tolerance as an attitude or nature of respect and respect for others and multicultural education that emphasizes the principles of equality. The author states four ways that can be taken in maintaining tolerance through multicultural education, namely deepening the meaning of tolerance in learning, providing discussions about various cultures, increasing awareness of the social sphere, and trying to open the thinking patterns of students so that echo chambers do not occur.